2016
DOI: 10.18522/2073-6606-2016-14-3-101-111
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cluster efficiency measurement tool

Abstract: This study aims at verifying the validity of cluster efficiency measurement tool. In previous study benchmarking was employed (Tvaronavičienė et al., 2015) IntroductionAccording to Karaev et al (2007), clusters are recognizable as an important instrument for improving SMEs productivity, innovativeness and overall competitiveness through overcoming their size limitations. Although there are many various studies conducted in different countries but a common understanding of the cluster concept has not been ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 16 publications
0
19
0
2
Order By: Relevance
“…Literature analysis reveals that clusters and cluster organizations are sector sensitive. The previous studies (Razminienė, Tvaronavičienė & Zemlickienė, 2016;Tvaronavičienė, Razminienė & Piccinetti, 2015;Tvaronavičienė, 2017) showed that every cluster differs depending on its sector. Therefore, involvement in circular economy should be measured according to the industry or type of activity for it is impossible to apply a universal model.…”
Section: Clusters In Literaturementioning
confidence: 94%
See 1 more Smart Citation
“…Literature analysis reveals that clusters and cluster organizations are sector sensitive. The previous studies (Razminienė, Tvaronavičienė & Zemlickienė, 2016;Tvaronavičienė, Razminienė & Piccinetti, 2015;Tvaronavičienė, 2017) showed that every cluster differs depending on its sector. Therefore, involvement in circular economy should be measured according to the industry or type of activity for it is impossible to apply a universal model.…”
Section: Clusters In Literaturementioning
confidence: 94%
“…There were several preceding attempts by the authors to compose a system of indicators for clusters' efficiency evaluation in the national level by identifying indicators and apllying benchmarking technique to verify the reliability of the methodology. A system of indicators which was previously suggested by the authors (Razminienė & Tvaronavičienė, 2018;Razminienė et al, 2016;Tvaronavičienė et al, 2015) needs to be supplemented by including indicators that enable to identify how engagement into circular economy adds to competitiveness of the companies belonging to the cluster.…”
mentioning
confidence: 99%
“…Although activities do not reveal definitive figures, they show more personal opinion than numbers in processes. Hence, processes must get more prominence in counting the cluster efficiency (Razminienė et al 2016). …”
Section: The Evaluation Of Certain Clusters' Performancementioning
confidence: 99%
“…Ключевые показатели эффективности по видам управления организацией [7] Помимо вышеуказанных, существуют следующие показатели: достижения конечного результата, внутренней и внешней среды. При этом они могут быть использованы для корректирующих действий, предупреждающих действий и мотивации [8].…”
Section: таблицаunclassified
“…Учитывая сферы воздействия и частные стратегии изменений, составим матрицу критериев и показателей (таблица 3). Матрица критериев и показателей с учетом частных стратегий изменений по основным сферам организации [8][9][10] T able 3 . The matrix of criteria and indicators, taking into account the private strategies of change in the main areas of the organization [8- Данные величины должны отвечать следующим требованиям:…”
Section: показатели экономичности потенциала и устойчивости развитияunclassified